Vertically oriented Sn3O4 nanoflakes directly grown on carbon fiber cloth for high-performance lithium storage. Issue 6 (30th April 2019) - Jia, Hongyun; Cao, Xinxin; Pan, Anqiang; Huang, Linjun; Yin, Bo; Chen, Jing; Tan, Xiaoping; Tang, Yan; Han, Mingming; Liang, Shuquan
Abstract : Flexible electrodes of vertically oriented Sn3 O4 nanoflakes grown on carbon fiber cloth were synthesized by a hydrothermal reaction, exhibiting superior electrochemical performance. Abstract : Tin-based oxides are considered to be promising candidates for lithium-ion battery anode materials due to their high theoretical capacities. However, the low conductivity and drastic volume expansion/contraction during the reaction with Li + ions greatly limit their practical applications. Herein, we have successfully grown vertically aligned Sn3 O4 nanoflakes on the carbon fiber cloth substrate by a hydrothermal method, referred to as Sn3 O4 @CFC. As a binder-free flexible anode for LIBs, this composite can not only accommodate the structural strain upon cycling, but also improve the electrical conductivity. As a consequence, the Sn3 O4 @CFC electrode manifests high specific capacity and good cycling stability. It exhibits a high specific capacity of around 1500 mA h g −1 at 100 mA g −1, superior rate capability (835.6 mA h g −1 at a high current density up to 2000 mA g −1 ) and good cyclic stability with 66.2% capacity retention over 200 cycles at 1000 mA g −1 .